Cheiloscopy Versus Palatoscopy For Sex Determination In Indian Population – A Systematic Review - Pagare, Sandeep; Pol, Bhavika; Manoj, Reema; Anand, Raj; Shetty, Naveen; Waghmare, Mandavi (Journal of Neonatal Surgery, 2025)
Background: To determine a person's gender, forensic anthropology has traditionally used physical criteria such as bone characteristics, cranial morphology, and odontometric measures. These strategies have proven to be beneficial in a variety of countries, although they have limitations. Non-invasive procedures such as cheiloscopy and palatoscopy can be investigated as alternatives to conventional methods, and in certain situations, they may be more successful. Objectives: The study's goal is to compile research on sex identification using cheiloscopy and palatoscopy in India, evaluate their efficacy in detecting sexual orientation, and identify potential barriers. Methods: A comprehensive search of electronic databases, including PubMed, Scopus, and Web of Science, was conducted to identify relevant studies published up to September 2022. Data extraction and quality assessment were performed, and the results were synthesized through a systematic approach. Results: The results indicated that both cheiloscopy and palatoscopy show promise as methods for sex determination in the Indian population. Cheiloscopy demonstrated a sensitivity range of 70% to 92% and a specificity range of 72% to 95%. Palatoscopy showed a sensitivity range of 67% to 88% and a specificity range of 68% to 90%. The effectiveness of these methods varied depending on the sample size and the specific Indian population group studied. Conclusion: Cheiloscopy and palatoscopy are effective forensic dentistry tools for identifying human remains and gender, but their utility depends on age, technology, and cultural differences.